METODE PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Regita Nazwa Sahara; Neng Gina Sonia; Nips Ajijaya Sampurna; Nurfitria (Bajang Institute, 2024)
This research aims to identify and implement innovative Indonesian language learning methods at the elementary school (SD) level. By considering the complexity of language teaching at the elementary level, this research investigates various learning methods that can improve elementary students' understanding and mastery of Indonesian. The findings reveal that an approach integrating technology, educational games, and context-based teaching materials can be effective in enhancing students' interest and comprehension of the Indonesian language. The use of interactive learning media, such as smartphone applications and educational games, can provide enjoyable and motivational learning experiences for students. This research contributes to the development of Indonesian language learning methods at the primary school level, suggesting an approach that focuses on student engagement and the integration of technology as a teaching aid. By implementing innovative learning methods, it is expected to improve students' language skills and create a more dynamic and engaging learning environment in primary schools